27. USTAZ HANAFI HAJI AHMAD: CHAMPIONING NATIONALISM, CULTURE, AND ISLAMIC VALUES IN SENI SILAT CEKAK MALAYSIA - Maoinser, Mohd Azuwan; Mohd Rosdi, Nadhirah; Abdullah, Abdul Hazim; Mohd Zainudin, Anis Suria (Journal of Islamic, Social, Economics and Development, 2024)
Ustaz Hanafi has fostered a sense of unity among members of the Persatuan Seni Silat Cekak Malaysia (PSSCM), not only by nurturing expertise in silat but also by instilling a deep sense of national pride. This paper offers insights into Ustaz Hanafi's philosophy of nationalism, focusing on his efforts to cultivate love for the nation among PSSCM members. Through interviews with 15 PSSCM members directly mentored by Ustaz Hanafi, this study highlights his national consciousness, exemplified by one of PSSCM's core principles: "do not denigrate other authentic Malay silat." Ustaz Hanafi's patriotism is evident in his choice to use "Malaysia" rather than his own name (Hanafi or Ustaz Hanafi) in PSSCM's branding, emphasizing that this martial art belongs to the country and its citizens. To preserve cultural heritage and promote knowledge advancement, Ustaz Hanafi champions the philosophy that "Science and technology can be learned anywhere; but culture remains ours," reminding PSSCM members to always uphold Malay culture wherever they may be. Not only does Ustaz Hanafi uphold Malay culture, but he also ensures that it aligns with Islamic principles, such as showing high respect for the female community in learning Seni Silat Cekak Malaysia (SSCM). Female trainers are provided for female students to prevent any abuse towards women by men. Despite being a nationalist, Ustaz Hanafi incorporates Islamic practices into Seni Silat Cekak Malaysia (SSCM), making this martial art accessible to people of all races worldwide. In conclusion, this study recognizes Ustaz Hanafi as a dedicated individual with deep love for religion, nation, and country. His steadfast commitment to instilling noble values in PSSCM members underscores his principled and unwavering character.